2008
DOI: 10.3748/wjg.14.3672
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid induces apoptosis through inhibition of nuclear factor kB in pancreatic cancer cells

Abstract: AIM:To determine the effect of ellagic acid on apoptosis and proliferation in pancreatic cancer cells and to determine the mechanism of the pro-survival effects of ellagic acid. METHODS:The effect of ellagic acid on apoptosis was assessed by measuring Phosphatidylserine externalization, caspase activity, mitochondrial m e m b ra n e p o t e n t i a l a n d D N A f ra g m e n t a t i o n ; and proliferation by measuring DNA thymidine incorporation. Mitochondrial membrane potential was measured in permeabilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(107 citation statements)
references
References 28 publications
3
103
0
1
Order By: Relevance
“…It has been shown to reduce the incidence of a variety of carcinogen-induced tumors 20 . The anticarcinogenic effect of EA was shown in several types of cancers [21][22][23][24][25] . In our study we observed, EA at 25-200µM strikingly reduced the cell viability of U251 cells, suggesting the anti-proliferative efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to reduce the incidence of a variety of carcinogen-induced tumors 20 . The anticarcinogenic effect of EA was shown in several types of cancers [21][22][23][24][25] . In our study we observed, EA at 25-200µM strikingly reduced the cell viability of U251 cells, suggesting the anti-proliferative efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical anti-cancer drugs are used for causing cell death by induction of apoptosis in cancer cells (38,39). DAS has been showed to promote immune responses in leukemic mice in vivo (29).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ellagic acid in human plasma is largely a consequence of their hydrolysis facilitated by physiological pH and activity of several colon microbiota [6]. Ellagic acid was found to reduce cancer cell growth by induction of apoptosis [21,22] and to exert various antiinflammatory effects [6]. The other biologically important phenolics are flavonol glycosides (including quercetin-3-glucuronide and kaempferol-3-glucuronide), flavan-3-ols (mainly (+)-catechin) and hydroxy acids (gallic, salicyl, caffeic, p-hydroxybenoic, ferulic, p-cumaric, cinnamic and vanillic acids) [5,12].…”
Section: Introductionmentioning
confidence: 99%